The Relationship Between The Role Of Parents To The Growth Of Preschool Children In Kalimati Village, Tarik District Sidoarjo Year 2020 - Sri Yulis Setyaningsih; Erma Retnaningtyas (Journal for Research in Public Health, 2023)
Growth and development are processes that occur in living things. Growth is said to increase in physical size, due to the multiplication of cells and the increasing number of substances between cells. Growth and development concern all aspects of progress achieved from the womb to adulthood (Irianton Aritonang, 1996). Based on an initial survey with interview techniques for 10 respondents conducted at the Posyandu Kalimati in January 2020 showed that there are still many toddlers with poor nutritional status. The purpose of this study was to Analyze the Relationship of the Role of Parents to the Growth of Preschool Children in Kalimati Village, Tarik Sidoarjo District in 2020. The design of this study included a cross sectional analytic study with a survey approach. The population in this study were all parents and toddlers in the Kalimantan village of Tarik Sidoarjo in 2020, amounting to 30 respondents. Samples were taken by simple random sampling technique taken by Slovin formula, amounting to 28 respondents. The variables of this study are the role of parents on an ordinal scale and the growth of preschool-aged children on an ordinal scale. This research was conducted in Kalimati Village, Tarik Sidoarjo District, from January to July 2020 using a questionnaire sheet and observation sheet. In collecting data from respondents the next step taken by researchers is data processing by editing, coding, scoring, tabulating, data entry, and cleaning. Data analysis in this study used the contingency coefficient test. Based on the results of statistical tests using the Spearman rank test, it is known that ρ-value <0.05, with a value of 0.009 <0.05, it can be concluded that H0 is rejected and H1 is accepted, which means that there is a relationship between the Role of Parents Against the Growth of Preschoolers. The determining factor for a child's physical and mental development is the role of parents, especially the role of a mother, because the mother is the first and foremost educator of children born to adulthood. The role of parents in the growth of pre-school children is very important. Nutritious and balanced food is needed by the body so that the nerve cells of the brain can grow optimally.